Time dependent changes in oxidative metabolism during chronic diabetes in rats - Sasvári, Mária; Nyakas, Csaba (Acta Biologica Szegediensis, 2003)
The stability and capacity of antioxidant status during chronic diabetes seriously influence the outcome of the long-term complications caused by oxidative stress. In the present study we investigated the effects of chronic streptozotocin-induced diabetes on the parameters of antioxidant status: activity of scavenging enzymes, gluthation-related and total antioxidant capacity, and degree of lipid peroxidation. Changes in the activities of superoxide-dismutase (SOD), glutathione peroxidase (GSH-Px), gluthatione reductase (GSH-R), and catalase, and in the content of reduced gluthation (GSH), and oxidised gluthatione (GSSG), and in the ratio of GSH/GSSG in blood samples were determined by means of biochemical methods. The degree of lipid peroxidation was measured via thiobarbituric acid assay (TBARS). Hyperglycaemia, ketosis and the accumulation of glycated proteins were estimated by measuring blood glucose, 3-OH-butirate, fructosamine and haemoglobin A1C. In the course of chronic insulin-dependent diabetes, i.e. at 2 and 7 days, 10 weeks, and 6 and 8.5 months after streptozotocin injection, hyperglycaemia slightly while ketosis markedly attenuated. Lipid peroxidation was also attenuated. SOD activity decrease in the acute phase only. The activity of GSH-Px increased in the early phase while that of GSH-R mostly decreased in the chronic phase. GSH and GSSG concentrations moved into opposite direction in a time dependent manner. In conclusion, in chronic diabetes an attenuation of severity of diabetes was present throughout the post-injection period, which was well reflected in the improved antioxidant status and capacity.